XI International Conference on Structural Dynamics 2020
DOI: 10.47964/1120.9312.19021
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Generative Adversarial Networks in Structural Health Monitoring

Abstract: In the current work, the use of generative adversarial networks (GANs) in a simulated structural health monitoring (SHM) application is studied. A specific type of GAN is considered, aiming at a disentangled representation of underlying features and clusters of data through some latent variables. This idea could prove useful in SHM, since explanation of how damage mechanisms or environmental conditions affect a structure may be exploited in order to monitor structures more effectively. In a simulated mass-spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…With training, the generator improves and produces images that are more real. The idea of using GAN for SHM systems was studied by Tsialiamanis et al 239 It was demonstrated that with prior knowledge, GAN can reflect damage characteristics via categorical and continuous variables despite the presence of EOFs. Therefore, GAN can be promising in training large datasets.…”
Section: Neural Network (Supervised/unsupervised)mentioning
confidence: 99%
“…With training, the generator improves and produces images that are more real. The idea of using GAN for SHM systems was studied by Tsialiamanis et al 239 It was demonstrated that with prior knowledge, GAN can reflect damage characteristics via categorical and continuous variables despite the presence of EOFs. Therefore, GAN can be promising in training large datasets.…”
Section: Neural Network (Supervised/unsupervised)mentioning
confidence: 99%
“…To identify and clarify the position of GANs in the civil SHM field, in terms of the type of GAN applications studied by the researchers, an illustrative figure is made (Figure 9) which shows the classification of the applications of GANs in civil SHM and the corresponding studies with the GAN models used in each study. As the main concept of GAN is to learn data domain and data generation, some studies solely studied data generation [ (Kanghyeok and do Hyoung, 2019;Xiong and Chen, 2019;Zhang and Wang, 2019;Tsialiamanis et al, 2020;Xu et al, 2021;Yu et al, 2021;Tsialiamanis et al, 2022a;Heesch et al, 2021;Colombera et al, 2021;Luleci et al, 2022b;Luleci et al, 2023)] (a total of 11 studies) by using original GAN or other GAN variants. Thus, the data generation category is separated from other categories.…”
Section: Generative Adversarial Network In Civil Structural Health Mo...mentioning
confidence: 99%
“…The authors in one study (Tsialiamanis et al, 2020) investigated an application of InfoGAN in SHM where they demonstrated that InfoGAN can capture the damage acceleration responses in a simulated mass-spring application. They induced different extents of stiffness reductions as damage to the system.…”
Section: Studies Published In 2020 (2 Papers)mentioning
confidence: 99%